A retrospective study of the eGFR differences between the 2021 CKD-EPI Equation and the MDRD equation in Black and White Patients. (9th November 2022) - Chang, Jeffrey; Redden, David; Lima, Jose; Reddy, Vishnu; Cao, Liyun
Abstract: Objectives: In implementing the 2021 CKD-EPI without race equation in our institution, we sought to investigate the differences between the new CKD-EPI equation and the current MDRD equation to assist clinicians in transitioning to the new equation. Methods: A retrospective study was performed in patients with eGFR<60 ml/min/1.73 m2 calculated by MDRD. Stata was used to analyze the eGFR calculated by the two equations and measure the differences according to respective categories. Results: eGFRs calculated by the 2021 CKD-EPI without race equation were well correlated to eGFRs calculated by the MDRD. However, notable differences were observed. Compared to the MDRD, the CKD-EPI w/o race equation for Black males with a serum creatinine less than 1.5 yielded decreased eGFR results with mean negative differences of -4.49 (18-60 years old), -6.43 (60-80 years old), and -8.87 (>80 years old). For serum creatinine cohorts between 1.5 to 2.0 and greater than 2.0, the differences were -3.35, -5.46, -7.48 and -1.86, -3.40, -4.14, respectively. A similar trend was noted in Black females. For those with a serum creatinine less than 1.5, the CKD-EPI equation yielded mean negative differences that increased with advancing age: -2.56, -4.74 and -7.27. For serum creatinine between 1.5 to 2.0 and greater than 2.0, the negative differences were -2.31, -3.73 and -5.28 and -1.30, -2.06 and -2.70, respectively. Therefore, in Black patients, the mean eGFR difference between the two equations increased as age increased and serum creatinine level decreased. In contrast, the CKD-EPI equation for White males with a serum creatinine less than 1.5 yielded increased eGFR results with mean positive difference of 7.22 (18-60 years old), 4.09 (60-80 years old), and 1.26 (>80 years old). For serum creatinine cohorts between 1.5 to 2.0 and greater than 2.0, the differences were 5.15, 2.54 and 0.18 and 2.01, 0.69 and -0.15, respectively. Similarly, White females had mean positive differences of 8.09 (18-60 years old), 4.61 (60-80 years old) and 2.00 (>80 years old). For cohorts with serum creatinine between 1.5 to 2.0 and greater than 2.0, the positive differences were 4.21, 2.24, 0.51 and 2.02, 0.82, 0.10. Therefore, in White patients, the difference of eGFR between the two equations increased as age decreased and creatinine level decreased. Conclusions: Although the 2021 CKD-EPI equation strongly correlated with the MDRD, distinct differences exist. In our study, Black males and females exhibited a negative difference of around -5.0 and -4.0, respectively. The difference in eGFR was greater in those of older age and serum creatinine less than 1.5. Meanwhile, White males and females exhibited a positive difference of around 2.5 and 2.7. The difference in eGFR was greater in those of younger age and serum creatinine less than 1.5.